Biodiversity of nekton in the Barumun Watershed, Labuhanbatu District, North Sumatra, Indonesia - Desrita Desrita; ‪Ridahati Rambey‬; ‪Ahmad Muhtadi; Onrizal Onrizal; Vindy Rilani Manurung; Julia Syahriani Hasibuan; Isten Sweno Tamba (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Dersita, Rambey R, Muhtadi A, Onrizal O, Mamurung VR, Hasibuan JS, Tamba IS. 2022. Biodiversity of nekton in the Barumun Watershed, Labuhanbatu District, Indonesia. Biodiversitas 23: 2426-2432. Biodiversity is a very valuable source of germplasm for science and sustainable development. Therefore, research on freshwater biodiversity is very important to support the sustainability of this development. The research investigated three rivers in South Labuhanbatu District, North Sumatra, Indonesia: Barumun, Tasik, and Titi Kembar rivers. This investigation aims to ascertain the composition, distribution, and variety of nekton. From April to August 2020, the trial lasted five months. Nekton samples were collected with the aid of nets and fishing nets. While installed in the afternoon, the nets are removed the following day. Additionally, at each observation point, stocking nets were operated three times. The investigation discovered 38 fish species and one shrimp species. Two species of fish discovered, are protected by the government of the Republic of Indonesia. Both fish species are Tenualosa terubuk, a fish with little protection, and Fluvitrygon signifer, a ray fish with complete protection. The study site's sole shrimp species was the gigantic prawn Macrobrachium rosenbergii in the Barumun river. The index of nekton diversity discovered in the three rivers was not identical. Compared to other rivers, the Tasik river station has a high diversity. This makes the Tasik river rich in fish compared to the Barumun and Titi Kembar rivers. The Tasik river is recommended as water suitable for fish life from these results.